An Integra Ted Approach to Service Marketing: A Book of Readings on Marketing of Library and Information Services. Edited by Dinesh K. Gupta and Asbok Jambhekar. 2003, Allied Publishers Pvt. Ltd., ISBN: 81-7764-417-3mumbai, Viii+ 328 paper Back), Rs. 495 - Nikam, Khaiser (Journal of Information and Knowledge, 2014)
No abstract